A 40-year-old male with recurrent oro-genital ulceration and joint pain - Chowdhury, Pavel; Azad, Md Abul Kalam; Aftab, Kazi Ali (Bangladesh Journal of Medicine, 2024)
Bechet’s disease is a systemic inflammatory disorder of unknown aetiology. Early proper diagnosis and treatment is of paramount importance as disease course and management protocol varies among the possibilities. Here, we are reporting a young patient without co-morbidity, who has been labelled as Bechet’s disease after a long journey with diagnostic uncertainty and managed accordingly with positive outcome. Mr. X, 40-year-old male construction worker without any co-morbidities presented with the complaints of multiple recurrent painful, non-itchy, non-discharging oro-genital ulcer along withasymmetrical multiple inflammatory joint pain predominantly involving large joint of lower limbs for 5 years which is more frequent in last 1 year. In addition to above mentioned features, he had mechanical type of low back pain for last 3-4 years. Moreover, he gave history of bilateral painless red eye with blurring of vision for the last 7 months. Furthermore, he complained of significant weight loss for last 1 month. He denied any history of fever, skin rash, alopecia, photosensitivity, dysuria, bowel complaints or any contact to TB patient. Ironically, he visited multiple tertiary level hospital several times over last 5 years and underwent several investigations including skin biopsy and then, he was prescribed anti-TB medications for ulcer as well as methotrexate, sulfasalazine, hydroxychloroquine and NSAID for arthritis but was found inadequate response. On examination, pustular lesions over right tendoachilis and under surface of tongue, a healing ulcer in subcutaneous injection site; a left sided well-defined, firm, tender and irregularly indurated erythematous exudative as well as non-discharging buccal ulcer and of course a painful scrotal ulcer were found. Additionally, he had features of bilateral inflammatory knee joint arthritis and hypopion on eye examination with positive pathergy test. His investigations illustrated microcytic hypochromic anaemia on PBF with increased level of CRP (102) and positive MT, ANA (neocleoli pattern), ENA (SS-A/Ro-52KD), HLA-B27; whereas, synovial fluid showed increased WBC with predominant lymphocytes and negative Gene-Xpert testing. It should be noted that, his HLA-B51, RA, Anti-CCP, Anti-dsDNA, Anti-phospholipid Ab, VDRL, TPHA, HIV, HBsAg, Anti-HCV were negative. Nevertheless, his Ultrasonogram of both knee revealed synovitis and osteophytes; scrotal ulcer biopsy showed chronic non-specific ulcer, endoscopy and colonoscopy was normal. Lastly, his MRI of L/S spine and SI joints showed only degenerative changes without any features of sacroiliitis.Our patient was diagnosed with Bechet’s disease (by fulfilling ISGDx criteria), therefore, he was commenced on methotrexate 15mg OD and colchicine 0.6mg OD for systemic features and topical steroid for mucocutaneous ulcers. Unfortunately, his treatment response was unsatisfactory even after 6 months of continuation. Eventually, azathioprine 50mg BD instead of MTX was initiated along with continuation of colchicine 0.6mg OD. A scheduled follow up after 3 months revealed resolution of oro-genital ulcers, fatigue, inflammatory arthritis and uveitis. In conclusion Bechet’s is a vasculitis with multisystem involvement. Bechet’s mimicking conditions like SLE and Seronegative arthritis with non-specific mucocutaneous ulcers can present in very similar pattern. Early diagnosis and appropriate treatment is critical for successful outcome. Clinicians should have high index of suspicion of Bechet’s disease in patients with oro-genital ulceration, asymmetrical large joint arthritis, uveitis and HLA B-27 positivity. Our patient showed satisfactory treatment response with azathioprine and colchicine regimen at last. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 175-176